2012
DOI: 10.3109/13668250.2012.743650
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive examination of the types of relationships formed between children with developmental disability and their closest peers in inclusive school settings

Abstract: M. (2013). A descriptive examination of the types of relationships formed between children with developmental disability and their closest peers in inclusive school settings. Journal of Intellectual and Developmental Disability, 38 (1), 1-11.A descriptive examination of the types of relationships formed between children with developmental disability and their closest peers in inclusive school settings AbstractBackground One of the most commonly cited rationales for inclusive education is to enable the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…There were 210 confirmed friendships between students with and without severe disabilities across these studies. Moreover, this number is underestimated because one study did not indicate a specific number of confirmed friendships though a majority of its students with severe disabilities had developed positive peer relationships and friendships with TD peers (Webster & Carter, 2013a). Staub et al's (1994) four portraits of friendship included descriptions of "rich and varied relationships" (p. 323).…”
Section: The Nature Of Friendships Between Students With and Without mentioning
confidence: 99%
“…There were 210 confirmed friendships between students with and without severe disabilities across these studies. Moreover, this number is underestimated because one study did not indicate a specific number of confirmed friendships though a majority of its students with severe disabilities had developed positive peer relationships and friendships with TD peers (Webster & Carter, 2013a). Staub et al's (1994) four portraits of friendship included descriptions of "rich and varied relationships" (p. 323).…”
Section: The Nature Of Friendships Between Students With and Without mentioning
confidence: 99%
“…Such mutual interest in others' play has also been seen to indicate 'a sense of we-ness experience difficulty in sustaining more intimate peer relationships (Guralnick 2006;Guralnick et al 2007;Webster and Carter 2013)?…”
Section: Discussionmentioning
confidence: 99%
“…Some longitudinal research has suggested that the sustainability of such relationships reduces significantly over time (Guralnick et al 2006) and if they do continue, greater intimacy and sophistication struggle to develop (Guralnick et al 2007;Webster and Carter 2013). A further suggestion is that for children identified with SEN, enduring friendships depend on the children in the relationship being at a comparable developmental level (Skinner, Buysse and Bailey 2004;Hollingsworth and Buysse 2009).…”
Section: Discussionmentioning
confidence: 99%